Phacoemulsificatıon and Intraocular Lens Implantation for the treatment of high myopia with cataract (Journal of National Institute of Ophthalmology, 2026)
Background: High myopia, defined as an axial length of ≥26.0 mm, is a common condition worldwide which increases the risk of cataract development. Phacoemulsification is a popular, safe, and effective surgical method for intraocular lens extraction, but cataract surgery in highly myopic eyes is risky procedure with common intraoperative and postoperative complications. Objective: To evaluate the outcomes and complications following phacoemulsification and intraocular lens implantation in eyes with cataract and high myopia. Methods: This was a prospective observational study performed among 50 eyes of 44 patients with cataract and high myopia who underwent phacoemulsification and intraocular lens implantation. Preoperative and postoperative uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA) were measured. Preoperative and postoperative refractive values were measured as spherical equivalent (SE), calculated as the summation of the spherical refractive value and half of the cylindrical value. High myopia was defined as AL ≥ 26.0mm and spherical equivalent (SE) ≤ −6.0 dioptres (D). Target postoperative refractions were within ±1.00 diopters (D). All patients were followed up for three months. Results: The mean age of the patients were 50.3 (±6.9) years where 28 (56.0%) patients were male. The mean axial length and IOL were 27.9 (±1.6) and 7.9 (±3.3) respectively. Among the 50 eyes of 44 patients, 33 (66.0%) had nuclear cataract. The mean pre-operative spherical equivalent was -11.0 (±1.9) which significantly decreased to -0.9 (±1.9) post-operatively (p